2016
DOI: 10.1016/j.jsbmb.2016.04.021
|View full text |Cite
|
Sign up to set email alerts
|

The hunt for a selective 17,20 lyase inhibitor; learning lessons from nature

Abstract: Given prostate cancer is driven, in part, by its responsiveness to androgens, treatments historically employ methods for their removal from circulation. Approaches as crude as castration, and more recently blockade of androgen synthesis or receptor binding, are still of limited use long term, since other steroids of adrenal origin or tumor origin can supersede that role as the ‘castration resistant’ tumor re-emerges. Broader inhibition of steroidogenesis using relatively nonselective P450 inhibitors such as ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 81 publications
0
36
0
Order By: Relevance
“…64 In particular, abiraterone acetate has recently been approved in the United States for the treatment of hormone-dependent and castration-resistant prostate cancer patients. 65 In addition, the inhibition of CYP17 by ketoconazole also exhibited tumor-suppressive effects in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…64 In particular, abiraterone acetate has recently been approved in the United States for the treatment of hormone-dependent and castration-resistant prostate cancer patients. 65 In addition, the inhibition of CYP17 by ketoconazole also exhibited tumor-suppressive effects in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that CYP17A1 upregulation confers drug resistance to glioblastomas by increasing DHEA synthesis [7,8]. Hence, we aimed to study whether abiraterone, a well-known CYP17A1 inhibitor [12], potentially suppresses glioblastomas. As shown in Figure 1A, abiraterone significantly inhibited the survival of T98G, A172, and patient-derived PT#3 glioblastoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we are not sure whether SAR1 is a novel substrate of CYP17A1, even though we found an interaction of CYP17A1 with SAR1. Through 17α-hydroxylase and 17,20 lyase activities, multiple steps of steroidogenesis require CYP17A1, including the production of 17α-hydroxy-pregnenolone and DHEA [12,16]. In contrast, whether the enzymatic activity of CYP17A1 is involved in protein interactions, or whether it participates in other cellular processes, remains largely unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the molecules VT-464 and galeterone are both pharmaceutical agents used to specifically target the 17,20-lyase reaction over 17α-hydroxylase activity. In contrast to abiraterone and orteronel, these newly described agents have an increased specificity towards 17,20-lyase, which results in the inhibition of testosterone synthesis while causing only minimal changes to patient cortisol levels (16).…”
Section: Androgen Signaling In Prostate Cancermentioning
confidence: 99%